Collaborative spectrum sensing by combining energy and cyclostationarity–based detection schemes. (18th September 2013) - Wang, Tsang–Yi; Hsu, Ming–Fong; Wu, Jwo–Yuh; Gao, Jian–Lang
In this paper, the problem of spectrum sensing in cognitive radio communication networks is considered. This paper proposes a robust decision fusion scheme that can perform well when interference caused by other sources is present. Specifically, the proposed detection scheme is based on fusing the local decisions from energy detectors and cyclostationarity–based detectors. The proposed fusion scheme is different from other power spectrum–sensing technology developed so far in that other fusion technologies are based on fusing the local decisions from the same type of detectors instead of the different types of detectors as considered here. The proposed scheme was compared with schemes fusing the same type of detectors, and the results show that the proposed scheme is more robust against possible interference.